EFFECT OF ETHICAL HUMAN RESOURCE MANAGEMENT PRACTICES ON THE FINANCIAL PERFORMANCE OF LISTED FIRMS IN THE NAIROBI SECURITIES EXCHANGE (NSE) - Ogwoka, Daniel Manduku; Namada, Dr. Juliana; Sikalieh, Dr. Damary (Human Resource and Leadership Journal, 2017)
Introduction: Despite the vast research on ethical leadership, so little is revealed concerning a quantified relationship between ethical human resource practices and enterprise financial performance commensurate to the associated moral practices presented throughout the literature. Purpose: Accordingly, this study sought to evaluate the direct impact of ethical human resource practices on the financial performance (measured by ROA) in the listed firms in Kenya by propounding a directly proportional relationship respectively, with the rather being the dependent variable. Research Methodology: A causal research design was adopted, and the relationships were evaluated through correlation and regression analysis. Sixty-four CEOs from the listed firms in Kenya participated in the research by filling online questionnaires while data analysis was done using the Statistical Package for Social Scientists (SPSS). Findings: The results revealed a significant relationship between ethical human resource practices and financial performance which was quantified through a linear regression model. The study recommended scrupulous adherence to the ethical HR practices and suggested replication of the study to other non-listed firms and the public sector. Contribution: The study findings indicated that financial performance is high when firms always adhere to labor laws, recruitment practices and firm's policy when recruiting employees. It, therefore, recommends that the firms should always adhere to their labor laws, recruitment practices, and the firm's recruitment policy which should be based on academic qualifications, skill/talents, and experience when hiring employees.